Transformational Leadership and Project Success: Serial Mediation of Team-Building and Teamwork - Ali, Hussain; Chuanmin, Shuai; Ahmed, Mansoor; Mahmood, Arshad; Khayyam, Muhammad; Tikhomirova, Anna (Frontiers in Psychology, 2021)
This research investigates the impact of transformational leadership style on project success in the indirect effect of serial mediation of team-building and teamwork quality. A quantitative research approach was used for this study. Data were gathered from 374 professional information system development (ISD) project managers in Pakistan. The hypotheses were tested using regression analysis with bootstrapping. Both team-building and teamwork independently and serially mediate the relationship between the project manager's transformational leadership and project success, respectively. The project manager's transformational leadership style intensifies the success of the project with team-building practices and quality of teamwork. Transformational leadership boosts teamwork quality in terms of communication, coordination, and cohesion to achieve a successful project. The findings suggest that transformational leadership associated with project success through serial mediation of team-building and teamwork. No research to date has used this nascent methodology to explore the association between transformational leadership and project success.